Identification of PEKKA Characteristics for the Women Empowerment Strategy in Sumedang Regency - Ferdiansyah, Hadi (The Journal of Indonesia Sustainable Development Planning, 2022)
Gender income disparity is one of the challenges in realizing community welfare in the Sumedang Regency. PEKKA worker is one of the vulnerable objects that need to be improved by the government of Sumedang Regency. This study aims to identify the individual characteristics of PEKKA to determine goals and priorities for women’s empowerment strategies. This study’s method is quantitative research in the form of a description with numbers or numerals (statistics). Reference studies that corroborate the analysis complement this study’s method. The analysis describes the characteristics of female heads of household in Sumedang Regency. The results showed that PEKKA in Sumedang Regency dominates by middle-aged and older women. Their level of education and competence is low, so they commonly work in the informal sector as unassisted entrepreneurs and in the formal sector as laborers. These characteristics are factors that cause their common welfare. Therefore, the PEKKA Empowerment Program in Sumedang Regency needs to involve other regional government affairs, namely Education, Health, Social, Labor, Communication and Information, Cooperatives, Small and Medium Enterprises, Agriculture, and Fisheries. Through this strategy, the PEKKA Empowerment Program can be right on target to encourage the realization of the welfare of the people of Sumedang Regency.